Pesantren-based psychosocial-spiritual therapy - Musyirifin, Zaen; Sari, Ferra Puspito; Kharir, Ari Muhammad (Jurnal Ilmu Dakwah, 2023)
Purpose – the purpose of this study is to identify the application of Psychosocial-spiritual in rehabilitation pesantren for people with mental disorders and for former drug addicts as well as to find the strengths and weaknesses of pesantren-based Psychosocial-spiritual.Method – The research method used was qualitative descriptive with the subject of Pondok officials and the students. Data collection was through interviews, observation, and documentation. The research location was in a pesantren specific for people with mental disorders and drug rehabilitation. Data analysis techniques in this research interactive model include data reduction, data presentation, and conclusion.Result  -  Psychosocial-spiritual therapy is related to some personality aspects, are psychology, social, and religion Psychosocial-spiritual therapy method found was andragogy, problem-solving, and psychosocial-spiritual.Implication – Psychosocial-spiritual, which integrates psychosocial and psychospiritual, could support rehabilitation for people with mental disorders and former drug addicts.Originality – This is the first research on psychospiritual therapy for people with mental disorders and former drug addicts.***Tujuan – Tujuan penelitian ini untuk mengetahui penerapan terapi psikososiospiritual di pesantren rehabilitasi bagi ODGJ dan mantan pecandu narkoba, serta menemukan kekurangan serta kelebihan terapi psikososiospiritual berbasis pesantrenMetode – Metode penelitian adalah deskriptif kualitatif, dengan subjek pengurus pondok dan santri bina. Pengumpulan data melalui wawancara, observasi dan dokumentasi. Lokasi penelitian dilakukan di jenis pesantren yaitu pesantren khusus orang dengan gangguan jiwa, rehabilitasi narkoba. Teknik analisis data dalam penelitian ini menggunakan model interaktif, yang meliputi reduksi data, penyajian data dan penarikan kesimpulan .Hasil  -  Terapi Psikososiospiritual berkaitan dengan beberapa aspek kepribadian, yaitu psikologis, sosial dan religious. Metode terapi psikososiospiritual yang ditemukan yaitu metode andragodi, problem solving dan psikoso-spiritual.Implikasi – Terapi psikososiospiritual yang merupakan integrasi dari psikososial dan psikospiritual ini dapat mendukung proses rehabilitasi pada ODGJ dan mantan pecandu narkoba.Orisinalitas – Penelelitian  mengenai terapi psikospiritual bagi ODGJ dan mantan pecnadu narkoba ini pertama kali diteliti.